Mortality from congenital malformations in England and Wales: variations by mother's country of birth. Issue 10 (October 1989) - Balarajan, R; Soni Raleigh, V; Botting, B
Abstract : Stillbirth and infant mortality from congenital malformations in England and Wales during 1981-5 was investigated according to the mother's country of birth. Significant differences remained after standardising for maternal age and social class. The highest overall mortality was in infants of mothers born in Pakistan (standardised mortality ratio 237), followed by infants of mothers born in India (standardised mortality ratio 134), East Africa (standardised mortality ratio 126), and Bangladesh (standardised mortality ratio 118). Caribbean and West African mothers showed an overall deficit. Mortality was inversely related to social class in all groups except the Afro-Caribbean. Infants of mothers born in Pakistan had the highest mortality in every social class except I, and for most anomalies investigated. Their ratios were particularly high for limb and musculoskeletal anomalies (standardised mortality ratio 362), genitourinary anomalies (standardised mortality ratio 268), and central nervous system anomalies (standardised mortality ratio 239). Our findings highlight the need for further research to identify the causes underlying these differences.